Queer approaches : emotion, expression and communication in the classroom - LaFollette, Kristin; Santavicca, Nicholas (Emerald Publishing Limited : Information Age Publishing, Inc., 2020)
"This edited collection supports queer educators and students, underscores the reasons society does not see LGBTQ representation in classroom spaces, and offers "queered" pedagogical approaches for teaching students from diverse backgrounds. This collection places value on every educator and student through prioritizing inclusivity, and the chapters carefully articulate what (queer) inclusivity is, why it matters for all educators, students, and administrators, and what can happen when inclusive environments are not created and/or sustained. When prompted to think about marginalized educators and students, most literature and research focuses on federal/state laws and instances of bullying. The chapters in this collection are farther reaching and provide (queered) solutions for these individuals' needs and challenges. This volume addresses the ability of the LGBTQ community to see themselves represented in the curriculum of schools, discussed in the language of society, and valued in all discourse settings. In addition, this volume uses queerness as a lens through which to reimagine classroom spaces and institutions of higher learning"--